Evaluation of Selected Herbicides on Weed Control Efficiency and Yield of Wheat - Mustari, Sobnom; Bari, Md. Nasimul; Islam, Md. Rafiqul; Karim, AJM Sirajul (Journal of Science Foundation, 2016)
Background: Weed control is an important issue for the proper growth of wheat. Objective: The purpose of the present study was to see the effect of selected herbicides on weed infestation behavior in wheat field; to determine the effect of herbicides on growth and development of wheat plants, and to evaluate the effect of herbicides on yield performance of wheat. Methodology: A field experiment was conducted at the Experimental Farm of the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, Bangladesh during November to May 2011 -2012. Four herbicides were tested at recommended dose alone and also coupled with supplemental hand weeding in wheat crop. In addition, a weedy check (control) was also imposed for treatment comparison. The herbicides were Pendimethalin, Carfentrazone-ethyl + Isoproturon, Carfentrazone-ethyl and 2,4-D. In this way, nine treatment combinations were arranged in the RCBD experiment with three replications. Result: Carfentrazone-ethyl performed the best in terms of weed control efficiency (79.68%), while Pendimethalin performed the worst (52.74%). Carfentrazone-ethyl + Isoproteuron contributed to the highest tillers per unit area (226.3 m-2) and the highest total dry matter (1342 g m-2). Finally, Carfentrazone-ethyl + Isoproteuron also contributed to the highest grain yield of 3.56 t ha-1 with the highest harvest index of 0.42. Carfentrazone-ethyl + Isoproteuron accompanied by one hand weeding also contributed to statistically identical grain yield of 3.33 t ha-1. Single ingredient Carfentrazone-ethyl alone and when accompanied with one hand weeding also contributed to statistically identical grain yields of 3.26 t ha-1 and 3.46 t ha-1, respectively. Conclusion: The study revealed that, combined ingredient herbicide Carfentrazone-ethyl + Isoproteuron as well as Carfentrazone-ethyl alone might used at field level due to their better weed control efficiency, favourable effect on crop growth and development and higher grain yield. Journal of Science Foundation 2014;12(2):27-33 DOI: http://dx.doi.org/10.3329/jsf.v12i2.27734